Early Cognitively Based Functional Limitations Predict Loss of Independence in Instrumental Activities of Daily Living in Older Adults. (22nd September 2015) - Lau, Karen M.; Parikh, Mili; Harvey, Danielle J.; Huang, Chun-Jung; Farias, Sarah Tomaszewski
Abstract: Older adults with early forms of neurodegenerative disease are at risk for functional disability, which is often defined by the loss of independence in instrumental activities of daily living (IADLs). The current study investigated the influence of mild changes in everyday functional abilities (referred to as functional limitations) on risk for development of incident functional disability. A total of 407 participants, who were considered cognitively normal or diagnosed with mild cognitive impairment (MCI) at baseline, were followed longitudinally over an average 4.1 years (range=0.8–9.2 years). Informant-based ratings from the Everyday Cognition (ECog; Farias et al., 2008 ) and the Instrumental Activities of Daily Living (Lawton & Brody, 1969 ) scales assessed the degree of functional limitations and incident IADL disability, respectively. Cox proportional hazards models revealed that more severe functional limitations (as measured by the Total ECog score) at baseline were associated with approximately a four-fold increased risk of developing IADL disability a few years later. Among the ECog domains, functional limitations in Everyday Planning, Everyday Memory, and Everyday Visuospatial domains were associated with the greatest risk of incident functional disability. These results remained robust even after controlling for participants' neuropsychological functioning on tests of executive functions and episodic memory. Current findings indicate that early functional limitations have prognostic value in identifying older adults at risk for developing functional disability. Findings highlight the importance of developing interventions to support everyday abilities related to memory, executive function, and visuospatial skills in an effort to delay loss of independence in IADLs. ( JINS, 2015, 21, 688–698)